Lens induced glaucoma: An experience in tertiary eye care center in eastern Nepal - Sitoula, Rakshya Pant; Sarkar, Indrajit; Nayak, Devdutta; Singh, Sanjay Kumar (Nepalese Journal of Ophthalmology, 2017)
Introduction: Lens Induced Glaucoma (LIG), is one of commonest cause of secondary glaucoma due to senile cataracts. The purpose of this study was to see the outcome of cataract surgery in patients with LIG. Methods: This was a prospective case series of 40 patients with LIG who presented to our hospital between April to June 2014. The purpose of this study was to look into the age and sex distribution, causes for delayed presentation, immediate post-operative visual outcome and the reasons for poor visual outcome. Result: There were 23 phacomorphic cases and 17 phacolytic glaucoma patients included in our study. The mean age at presentation was 63±10 years. Female to male ratio was 2.1:1. The majority of patients 57% presented after 2 weeks of symptoms and the reason for late presentation in more than half of the patients (52.5%) was financial constraints. At presentation, mean preoperative intra ocular pressure was 39±10 mm Hg. Following surgery, 36 of 40 eyes (90%) had an IOP less than 21 mm Hg at discharge. Visual acuity was either hand-movement or just perception of light in all eyes before surgery. At discharge, 26 of 40 operated eyes (65%) achieved 6/60 or better, 2 (5%) had less than 6/60 and 12 (30%) less than 3/60. The reasons for poor VA in these 12 patients were optic atrophy in 5 patients, uveitis in 5 patients, macular cause in one and corneal edema in one. Conclusion: Cataract surgery proves to be effective in lowering the Intraocular pressure and visual recovery in patients with lens induced glaucoma.